2015
DOI: 10.1051/0004-6361/201424896
|View full text |Cite
|
Sign up to set email alerts
|

First detection of the field star overdensity in the Perseus arm

Abstract: Aims. The main goal of this study is to detect the stellar overdensity associated with the Perseus arm in the anticenter direction. Methods. We used the physical parameters derived from Strömgren photometric data to compute the surface density distribution as a function of galactocentric distance for different samples of intermediate young stars. The radial distribution of the interstellar absorption has also been derived. Results. We detected the Perseus arm stellar overdensity at 1.6 ± 0.2 kpc from the Sun w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…Elias et al (2009) found that spatial distribution and kinematics of stars in Ori OB1 and Sco OB2 (distance from the Sun is 0.1-0.6 kpc (Mel'Nik & Dambis 2009)) would be explained if they were located close to the corotation zone. Antoja et al (2011) and Monguió et al (2015) studied stellar kinematics in the solar neighborhood and located the co-rotation radius at about 2 kpc beyond the solar circle. Griv et al Griv et al (2015) obtained the position of the co-rotation radius about 9.9 kpc.…”
Section: Discussionmentioning
confidence: 99%
“…Elias et al (2009) found that spatial distribution and kinematics of stars in Ori OB1 and Sco OB2 (distance from the Sun is 0.1-0.6 kpc (Mel'Nik & Dambis 2009)) would be explained if they were located close to the corotation zone. Antoja et al (2011) and Monguió et al (2015) studied stellar kinematics in the solar neighborhood and located the co-rotation radius at about 2 kpc beyond the solar circle. Griv et al Griv et al (2015) obtained the position of the co-rotation radius about 9.9 kpc.…”
Section: Discussionmentioning
confidence: 99%
“…Mishurov & Zenina (1999) and Dias & Lépine (2005) located it very close to the Solar orbit radius. However, Drimmel & Spergel (2001) located it at 6.7 kpc, Acharova et al (2012) at 7 kpc, and Monguió et al (2015) places it farther away than the Perseus arm. Recently, Michtchenko et al (2018) explained the moving groups observed in the solar neighborhood based on a model which places Rc close to the Sun.…”
Section: Introductionmentioning
confidence: 92%
“…To assess whether our data can expose such an effect, we examine the = 178 • sight line, since it is close to the radial direction that minimises shear due to Galactic rotation and more easily reveals low-amplitude perturbations that may be associated with spiral arm structure. Monguió, Grosbøl & Figueras (2015) used B4-A1 stars to find a stellar overdensity due to the Perseus spiral arm at a heliocentric distance of 1.6 ± 0.2 kpc in the anticentre direction, and Reid et al (2014) used parallaxes of 24 star forming regions to find the arm to be located at 2 kpc. The Perseus Arm is therefore located just short of the sampled region in this work.…”
Section: Spiral Arm Perturbationsmentioning
confidence: 99%